Which Program for Whom? Evidence on the Comparative Effectiveness of Public Sponsored Training Programs in Germany - Martin Biewen; Bernd Fitzenberger; Aderonke Osikominu; Marie Waller (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
We use a new and exceptionally rich administrative data set for Germany to evaluate the employment effects of a variety of public sponsored training programs in the early 2000s. Building on the work of Sianesi (2003, 2004), we employ propensity score matching methods in a dynamic, multiple treatment framework in order to address program heterogeneity and dynamic selection into programs. Our results suggest that in West Germany both short-term and medium-term programs show considerable employment effects for certain population subgroups but in some cases the effects are zero in the medium run. Short-term programs are surprisingly effective when compared to the traditional and more expensive longer-term programs. With a few exceptions, we find little evidence for significant positive treatment effects in East Germany. There is some evidence that the employment effects decline for older workers and for low? skilled workers.
Keywords: H43; J68; C14; 330; evaluation; multiple treatments; dynamic treatment effects; local linear matching; active labor market programs; administrative data